La documentación archivística en la obra de D. Agustín Millares Carlo - Moreiro González, Jose Antonio (Estudios humanísticos. Geografía, historia y arte, 2021)
Within the poligraphic dedication of Agustín Millares Carlo, we are going to deal this time with the description of bis works about archivistic sciences especially those dealing with the stock ketp in Spanish, Mexican and Venezolan archives, aboye all with protocols. Also bis important publications for the bibliographic consultation referring to spanish and hispanoamerican archives, particularly the council archives